Principles of immunopharmacology 3rd revised and extended edition - Nijkamp, F.P.; Parnham, Michael J.; SpringerLink (Online service). (Basel Boston Birkhäuser Basel, 2011)
Principles of Immunopharmacology provides a unique source of essential knowledge on the immune response, its diagnosis and its modification by drugs and chemicals. The third edition of this internationally recognized textbook has been revised to include recent developments, but continues the established format, dealing with four related fields in a single volume, thus obviating the need to refer to several different textbooks. The first section of the book, providing a basic introduction to immunology and its relevance for human disease, has been updated to accommodate new immunological concepts, including dendritic cells. The second section on immunodiagnostics offers a topical description of widely used molecular techniques and is followed by a systematic coverage of drugs affecting the immune system, including natural products. This third section contains 15 updated chapters, covering classical immunopharmacological topics such as anti-asthmatic, anti-rheumatic and immunosuppressive drugs, but also deals with antibiotics, plant-derived and dietary agents, with a new chapter on probiotics. The book concludes with a chapter on immunotoxicology and drug safety tests. Aids to the reader include a two-column format, glossaries of technical terms and appendix reference tables. The emphasis on illustrations, many of which have been redrawn for this edition, is maintained from the first two editions. The book is a valuable single reference for postgraduate medical and biomedical students, postgraduate chemistry and pharmacy students, researchers in chemistry, biochemistry and the pharmaceutical industry and researchers lacking basic immunological knowledge, who want to understand the actions of drugs on the immune system.
Introduction: Altering the chain of command in host defence -- Immunity: Hematopoiesis and lymphocyte development: an introduction -- T cell subsets and T cell-mediated immunity.-Antibody diversity and B lymphocyte-mediated immunity -- Dendritic cells -- Cytokines -- Innate immunity - phagocytes, natural killer cells and the complement system -- Inflammatory mediators and intracellular signalling -- Immune response in human pathology: Infections caused by bacteria, viruses, fungi, and parasites -- Immune response in human pathology: Hypersensitivity and autoimmunity -- Cancer immunity -- Neuroimmunoendocrinology.- Immunodiagnosis: Antibody detection -- Immunoassays -- Flow cytometry -- Microarrays --  Immunotherapeutics: Vaccines -- Plasma-derived immunoglobulins -- Anti-allergic drugs -- Drugs for the treatment of airway disease -- Perspectives of immunotherapy in the management of asthma and other allergic conditions -- Immunostimulants in cancer therapy -- Anti-infective activity of immunomodulators -- Immunopharmacology of probiotics and prebiotics -- Mild plant and dietary immunomodulators -- Influence of antibacterial drugs on the immune system -- Cytotoxic drugs -- Immunosuppressives in transplant rejection -- Corticosteroids -- Non-steroidal anti-inflammatory drugs -- Disease-modifying antirheumatic drugs -- Immunotoxicology -- Appendices -- Glossary -- Index.
Electronic reproduction.
Keywords: Immunopharmacology; Immunity -- Drug effects; Electronic books